Early surgical complications after gastrointestinal surgery and the factors of risk among patients treated at Tishreen university hospital . A retrospective cohort study - علوش علي (Latakia University Journal -Medical Sciences Series, 2022)
Background: Postoperative complications (POCs) are significant concerns to surgeons because of their possible fatality or long-term disabilities. This study aimed to investigate the early POCs of gastrointestinal surgery and its associated factors in patients treated in a teaching hospital (Tishreen University Hospital,Latakia,Syria). Materials and methods: A retrospective cross-sectional study from June 2016 to June 2021 was conducted at Tishreen University Hospital,Latakia,Syria . The patients’ characteristics, causative factors, primary treatment, and POCs were recorded from their medical profiles. Univariate analysis was utilized to identify the risk factors associated with gastrointestinal POCs within 30 postoperative days. Results: The 30-postoperative day mortality was 3.6%, and major POCs occurred in 22 (20%) patients. There is no statistically significant relationship between POCs and age, sex, smoking, comorbidities (diabetes mellitus, anemia, jaundice, heart disease), emergency cases, drain insertion, and operative time (p ˃ 0.05). There was a significant relationship between POCs and preoperative poor nutritional status, need for blood transfusion, major abdominal surgeries, iatrogenic injury, small bowel resection, reoperation, and history of the previous laparotomy (p ≤ 0.05). Conclusion: There is a significant relationship between preoperative poor nutritional statuses, need for blood transfusion, major abdominal surgeries, reoperation, small bowel resection, iatrogenic injury, previous laparotomy, and POCs across different gastrointestinal procedures. These factors should be assessed when auditing surgical outcomes.